2011
DOI: 10.1016/j.yjmcc.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Expression of slow skeletal TnI in adult mouse hearts confers metabolic protection to ischemia

Abstract: Changes in metabolic and myofilament phenotypes coincide in developing hearts. Posttranslational modification of sarcomere proteins influences contractility, affecting the energetic cost of contraction. However, metabolic adaptations to sarcomeric phenotypes are not well understood, particularly during pathophysiological stress. This study explored metabolic adaptations to expression of the fetal, slow skeletal muscle troponin I (ssTnI). Hearts expressing ssTnI exhibited no significant ATP loss during 5 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…It is unlikely though that an energy deprivation is responsible for the arrhythmias in the ssTnI model, which undergoes metabolic remodeling resulting in increased glycolysis compared to controls. We have previously demonstrated that TG-ssTnI hearts are highly resistant to global ischemia with preservation of ATP concentration as a result of increased glycolysis [22]. We think in the case of TG-ssTnI hearts it is highly unlikely that there are localized energy deficits, and that remodeling of Ca 2+ fluxes is more likely to be responsible.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is unlikely though that an energy deprivation is responsible for the arrhythmias in the ssTnI model, which undergoes metabolic remodeling resulting in increased glycolysis compared to controls. We have previously demonstrated that TG-ssTnI hearts are highly resistant to global ischemia with preservation of ATP concentration as a result of increased glycolysis [22]. We think in the case of TG-ssTnI hearts it is highly unlikely that there are localized energy deficits, and that remodeling of Ca 2+ fluxes is more likely to be responsible.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we have previously reported that compared to controls, TG-ssTnI cardiac myofilaments demonstrate a substantial increase in Ca 2+ -sensitivity [19], a resistance to desensitization by acidic pH [20], and a blunted response to changes in sarcomere length [21]. Hearts of TG-ssTnI mice are also significantly resistant to ATP loss in global ischemia associated with remodeling to a relatively high glycolytic phenotype compared to controls [22]. We studied isolated cardiac myocytes from relatively young mice (5~7 months old) and relatively old mice (11~13 months old).…”
Section: Introductionmentioning
confidence: 99%
“…This protein is usually expressed highly in the prenatal mammalian heart, but is rapidly downregulated after birth when hearts begin to express predominantly cTnI [19]. Transgenic mice overexpressing ssTnI in their hearts maintain ATP production during ischemia by upregulating glycolytic activity [39]. Expression of ssTnI in the adult mouse heart during heart failure can also help maintain systolic function during respiratory hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…This harsh, energetically constrained habitat of highly variable oxygen availability and high levels of carbon dioxide relative to that experienced above ground is, thus likely to have shaped both their metabolic physiology and their cardiovascular system. In many cardiovascular disease states, adult mammalian hearts, like those of healthy naked mole-rats, also have to contend with the stressful conditions of hypoxia and hypercapnia [23, 39, 45]. Such diseased states are also responsible for disrupting cardiac homeostasis and causing dysregulation of the contractile protein signature [39, 42, 43].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated that replacement of the adult isoform of cardiac troponin I (cTnI) with the isoform expressed in the fetal heart, slow skeletal troponin I (ssTnI), confers ischemic protection by delaying the decline in myocardial ATP levels 15 . ATP stores were maintained through an upregulation of the glycolytic rate during ischemia while no phenotype was evident at baseline.…”
mentioning
confidence: 99%